Signal loss - Disher, Garry (Disher, Garry. Inspector Hal Challis murder mystery, 2017)
A pair of hit men working a job for a meth kingpin have a very bad day, and the resulting bushfire draws attention to a drug lab and two burned bodies in a Mercedes. With meth-related crime on the rise, interdepartmental tensions mount, and Inspector Hall Challis soon finds himself fighting to keep control of his case. Meanwhile, Sergeant Ellen Destry is hunting for a serial rapist who is extremely adept at not leaving clues--